Characterization Of Microstructure And Fatigue Life Of CP Titanium Grade 2 Specimens Subject To Various Bending Processes - Fidder, H; Botes, A; Woudberg, S; McGrath, P J (WIT Transactions on Engineering Sciences, 2013)
This study focussed on an investigation into the fatigue behaviour of commercially pure (CP) titanium (Ti) grade 2 specimens produced by various bending (deformation) processes, i.e. mechanical bending, laser bending and laser-mechanical bending. Although published literature on the fatigue behaviour of components produced by laser forming is relatively limited, it was found that laser bending could improve the mechanical behaviour of such components. At high fatigue load settings the microstructure was the dominant contributor to crack initiation and crack growth. After the specimens were bent, residual stress analysis as well as a characterization of the microstructure was performed on the three bent samples as well as the parent plate. Mathematical equations were formulated and presented for the laser forming process for predicting the fatigue life of CP Ti grade 2. This study revealed that the laser forming process can be successfully used as a manufacturing method in the forming of CP Ti grade 2.